A concepção de relação com o saber de Bernard Charlot e seu potencial antropológico - formativo : um exame crítico sobre o discurso neoliberal da qualidade da educação - Silva, Eunice Gomes da (2025)
This thesis is based on the understanding that education constitutes an essential condition for human existence, configuring itself in a process of construction of meaning in the relationship of the subject with himself, with others and with the world, and is based on Bernard Charlot's Theory of Relation to Knowledge. The research problem arises from the following question: How does the Theory of Relation to Knowledge enable a critical analysis of neoliberal discourses on the quality of education and how does it allow us to think about a conception of education in an anthropological-formative sense? The study's general objective is to analyze the concept of quality in contemporary education, as outlined in neoliberal discourses, and, simultaneously, to examine its limits based on the anthropological-formative potential present in the Theory of the Relationship with Knowledge. The methodology used is qualitative research, of a bibliographic nature, anchored in the hermeneutic stance, aiming to critically interpret central texts by Charlot, as well as by complementary authors, such as Dardot and Laval, Biesta, Freire, Dalbosco, Cenci, among others. The thesis begins with a presentation of the general overview of the research and a critical analysis of the neoliberal discourses that shape the contemporary conception of quality in education. This analysis identifies discourses from other fields of knowledge that, when incorporated into the educational field under the banner of quality, produce significant impacts on pedagogical practices and the purposes of education. The thesis then examines the effects of business logic on education in greater depth, based on the reflections of Dardot and Laval, highlighting how this influence distances education from a formative, integral and human perspective. In the next step, the thesis seeks to understand which conception of education is made possible by the Theory of Relationship with Knowledge, thus reflecting on its formative potential to promote a less competitive and more supportive education. The final chapter delves deeper into the analysis of the anthropological-formative potential of this theory, investigating how it can contribute to the construction of new ways of thinking, understanding and evaluating education. As a result, the research proposes a renewed vision of education, based on ethical, social and anthropological values. It is concluded that Charlot's theory offers promising paths for the redefinition of education, placing the subject at the center of the formative process and promoting pedagogical reflections based on solidarity. In this sense, it aims to transform the subject's relationship with knowledge, with the world and with oneself, fostering an education capable of recognizing the human condition and the importance of others in the collective construction of knowledge, in a dialogical, supportive and truly humanized space.